Monte sagrado : Templo Mayor - López Austin, Alfredo; López Luján, Leonardo; Instituto Nacional de Antropología e Historia; Universidad Nacional Autónoma de México. Instituto de Investigaciones Antropológicas (Instituto Nacional de Antropología e Historia : Universidad Nacional Autónoma de México, Instituto de Investigaciones Antropológicas, 2009)
Study of the mythology and symbolism of mountains in the Mexica culture resulting from recent excavations of the Templo Mayor of México-Tenochtitlan. Analyzes the significance of recently discovered offerings, monolithic sculptures and objects found during the 10-year research project.
Keywords: Templo Mayor (Mexico City, Mexico); Aztec mythology; Aztecs : Mexico : Mexico City : Antiquities; asteekit; azteker; fornlämningar; muinaisjäännökset; mytologi; mytologia; Meksiko; Mexico